Curing through Ceramics: Influence of Different Light-Curing Units and Curing Modes on Bond Strength - Evonne Mei Jing Phua; John Neil Waddell; Joanne Jung Eun Choi (MDPI AG, 2022)
Objectives: To measure and compare the bond strength between three different types of ceramics and resin cement, as well as the degree of conversion of resin cement after using different light-curing units and curing modes. Methods: Three types of ceramics-Leucite-reinforced (Empress CAD), Lithium disilicate (Emax CAD), and Zirconia (Emax ZirCAD)-of varying thicknesses (1.5 mm and 2.0 mm) were bonded to a light-cure resin cement (Variolink Esthetic LC). Light-curing was carried out using a monowave LCU (3M Elipar DeepCure-S LED Curing Light with irradiance of 1470 mW/cm2) and with polywave LCU (Ivoclar Bluephase PowerCure) using High, Turbo, and 3 s curing modes, respectively (1200, 2100, 3000 mW/cm2). A chevron-notch bond strength test (total n = 288) was conducted to calculate the fracture energy and interfacial bond strength (J/m2). The degree of cure (%DC) of the residual resin cement on debonded surfaces was measured using Fourier Transform Infrared Spectroscopy (FTIR). Collected data were statistically analysed under SPSS ver. 27 by conducting an ANOVA and Bonferroni post hoc test. The mode of failure was established using a scanning electron microscope (SEM). Results: A significant difference in interfacial bond strength was found between the three types of ceramic material groups (p < 0.01). Cement cured through Empress that was 2 mm thick showed the highest bond strength (1.36 ± 0.46 J/m2), while the lowest was observed (0.26 ± 0.07 J/m2) in 2 mm Emax CAD using the 3 s mode. The use of different LCUs and curing modes had a significant influence on the %DC of resin cement seen in all groups, except 2 mm Emax ZirCAD. The dominant mode of failure for Empress, EmaxCAD, and EmaxZirCAD were cohesive, adhesive, and mixed, respectively. Conclusions: The type of ceramic and its thickness can significantly affect bond strength, and the results showed that polywave LCU is more effective than monowave LCU when curing through ceramics.